La Mosquée de Paris a-t-elle sauvé des juifs ? Une énigme, sa mémoire, son histoire - Ethan Katz (Diasporas: Circulations, Migrations, Histoire)
The 2011 French film Les Hommes Libres brought unprecedented attention to the story of the Grand Mosque of Paris as a haven for Jews during the Holocaust.  This article offers the first scholarly analysis of both the collective memory of this story, and the conflicting historical evidence around it.  The first section argues that discussions of the mosque’s wartime history are shaped by three larger historical debates, and have thus reached an impasse between mythology and silence.  The second half, seeking to move beyond such debates, turns to the historical record of the mosque’s conduct in Occupied France.  It illuminates the contradictory choices of the mosque and its rector, Si Kaddour Benghabrit, who acted simultaneously as an agent of collaboration, accommodation, and resistance.